Spinal fusion surgery use among adults with low back pain enrolled in a digital musculoskeletal program: an observational study - Yadav, Sandhya; Gold, Laura S.; Zaidi, Qasim Hassan; Hwang, Raymond; Lu, Louie; Wang, Grace (BMC musculoskeletal disorders, 2024)
To compare 12-month spinal fusion surgery rates in the setting of low back pain among digital musculoskeletal (MSK) program participants versus a comparison cohort who only received usual care. Retrospective cohort study with propensity score matched comparison cohort using commercial medical claims data representing over 100 million commercially insured lives. All study subjects experienced low back pain between January 2020 and December 2021. Digital MSK participants enrolled in the digital MSK low back program between January 2020 and December 2021. Non-participants had low back pain related physical therapy (PT) between January 2020 and December 2021. Digital MSK participants were matched to non-participants with similar demographics, comorbidities and baseline MSK-related medical care use. Spinal fusion surgery rates at 12 months post participation were compared. Compared to non-participants, digital MSK participants had lower rates of spinal fusion surgery in the post-period (0.7% versus 1.6%; p < 0.001). Additionally, in the augmented inverse probability weighting (AIPW) model, digital MSK participants were found to have decreased odds of undergoing spinal fusion surgery (adjusted odds ratio: 0.64, 95% CI: 0.51-0.81). This study provides evidence that participation in a digital MSK program is associated with a lower rate of spinal fusion surgery.